'The writings of querulous women': contraception, conscience and clerical authority in 1960s Britain. Issue 4 (11th September 2015) - Harris, Alana
Abstract: On 31 May 1964, Dr Anne Bieżanek travelled from Wallasey to Westminster Cathedral to attend Mass and receive Holy Communion. She was flanked by hoards of reporters, who over the previous six months had fueled extensive media coverage of her establishment of one of the first Catholic birth control clinics in the world, alongside her intertwined personal story of the physical and emotional strain caused by ten pregnancies. Repeatedly refused the sacraments by her local parish priest in consequence of these activities, and unable to gain satisfaction from the Bishop of Shrewsbury, Dr Bieżanek wrote to the Archbishop of Westminster to announce her intention to 'resolve the issue' through an ethical adjudication at the Communion rails. As the first sustained exploration of this exceptional woman and her sensational life story, this article examines Dr Bieżanek's private correspondence and public persona to illustrate the ways in which her idiosyncratic re-negotiation of spiritual and sexual politics was path breaking in articulating a 'modern' Catholic approach to love and sex and in anticipating the cacophony of such voices elicited by the Humanae Vitae encyclical in 1968. As such, it illustrates the form and force of contrasting and modulating Catholic discourses about love, marriage, and contraception in the post-war period and demonstrates the continuing and critical interplay of religion, infused with the insights of sexology and psychology, when negotiating the sexual and spiritual revolutions of the sixties.